Visual perceptual abilities in ASD across the lifespan: To build upon or to compensate for? - Falkmer, Torbjorn (The Autism Association of Western Australia (Inc), 2011)
ASD are best managed by building on strengths at an individual level, while compensating for weaknesses at the societal level. As such, the aim of the presented 5 year research program is to promote participation for children and adults with autism through the development of visually-based strategies to support their participation in driving and education. To date, little research has focussed on visual functions in relation to participation in everyday life for those with ASD. For example, it is still unclear if face processing is deviant within the whole spectra of autism. A greater understanding of visual search strategies and their impact on face recognition and recognition of facially expressed emotions in controlled experimental conditions is thus needed. An awareness of the visual search strategies is also a prerequisite for the development of interventions. The project relies heavily on eye tracking methodology, possible EEG usage in conjunction, simulator and on-road driving, in addition to traditional methods such as focus groups. The initial face scanning trails are already run. We have found less use of the Face Information Triangle, rendering a difference between the overall visual search strategies for information seeking in faces between adults with AS and their matched controls. In future intervention strategies, the distribution of fixations on facial details will be important to cue. The stability of our results across conditions warrants laboratory findings to be generalized to “real world” situations. The next step is to take these findings into the area of driving and certain areas of education, where spatial relationships are crucial for success. Furthermore, the impact of alternative visual scanning patterns on visual illusions will be addressed.